IN VITRO TOXICITY EVALUATION OF CULTURE FILTRATES OF FUSARIUM OXYSPORUM F. SP. LYCOPERSICI ON GROWTH AND PHYSIOLOGY OF TOMATO UNDER CHROMIUM (VI) STRESS - S. Khurshid; A. Shoaib; A. Javaid (Journal of Animal and Plant Sciences, 2014)
In vitro toxicological influence of culture filtrates of Fusarium oxysporum f. sp. lycopersici (Sacc.) Snyder & Hans was investigated on seed germination, seedling growth and physiology of tomato (Lycopersicum esculentum Mill.) under chromium(VI) stress. Original culture filtrates of the fungus and three concentrations of Cr(VI) viz. 50, 75 and 100 mg L-1 were used in laboratory bioassays either alone or in different combinations. Experiment was carried out at 25 ± 2 °C in triplicate using completely randomized design and different growth and physiological assays were recorded in 15-days old tomato seedlings. Germination, growth and biomass was declined significantly up to 40%, 85% and 70% due to original culture filtrate of the F. oxysporum and by 40-60%, 10-50%, 50-80% under combine stress of original culture filtrate of the fungusalong with increasing concentration of Cr(VI), and by 10-20%, 0-25% and 30-60% due to increasing concentration of Cr(VI) alone. Chlorophyll contents was significantly declined due to original culture filtrate of the F. oxysporum f. sp. lycopersici alone or combined with Cr(VI), while non-significantly different due to solitary effect of Cr(VI) over control treatments. Whereas, catalase and peroxidase activities increased significantly in treatments supplemented with Cr(VI) alone or combination with fungus and decreased due to culture filtrate of fungus alone as compared to control. The present study concluded that culture filtrates of F. oxysporum f. sp. lycopersici are hazardous to tomato seedlings either alone or in combination with Cr(VI).
Keywords: Chromium; fungal culture filtrates; Fusasium oxysporum; Lycopersicum esculentum; tomato